Outsiders : the humanity and inhumanity of giants in medieval French prose romance - Huot, Sylvia (Conway lectures in medieval studies., 2016)
"Giants are a ubiquitous feature of medieval romance. As remnants of a British prehistory prior to the civilization established, according to the Historium regum Britannie, by Brutus and his Trojan followers, giants are permanently at odds with the chivalric culture of the romance world. Whether they are portrayed as brute savages or as tyrannical pagan lords, giants serve as a limit against which the chivalric hero can measure himself. In Outsiders: The Humanity and Inhumanity of Giants in Medieval French Prose Romance, Sylvia Huot argues that the presence of giants allows for fantasies of ethnic and cultural conflict and conquest, and for the presentation--and suppression--of alternative narrative and historical trajectories that might have made Arthurian Britain a very different place. Focusing on medieval French prose romance and drawing on aspects of postcolonial theory, Huot examines the role of giants in constructions of race, class, gender, and human subjectivity. She selects for study the well-known prose Lancelot and the prose Tristan, as well as the lesser known Perceforest, Le Conte du papegau, Guiron le Courtois, and Des Grantz Geants. By asking to what extent views of giants in Arthurian romance respond to questions that concern twenty-first-century readers, Huot demonstrates the usefulness of current theoretical concepts and the issues they raise for rethinking medieval literature from a modern perspective. "In her beautifully written Outsiders: The Humanity and Inhumanity of Giants in Medieval French Prose Romance, Sylvia Huot organizes a wealth of material into a taxonomy of giants and their complex role in medieval French literature. Huot imaginatively uses that mapping to demonstrate the many ways in which the figure of the giant is a cultural fantasy through which medieval writers imagined the limits of personhood. Tracing that fantasy through medieval concepts of race and ethnicity, Huot makes an original and important claim not just about what giants do for medieval writers or their audiences, but also about the vulnerable boundaries of the human that are both put into question and reaffirmed by representations of giant outsiders."--Peggy McCracken, University of Michigan"--